2019
DOI: 10.1038/s41598-019-51823-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Turnip mosaic virus and its viral-like particles

Abstract: Turnip mosaic virus (TuMV), a potyvirus, is a flexible filamentous plant virus that displays a helical arrangement of coat protein copies (CPs) bound to the ssRNA genome. TuMV is a bona fide representative of the Potyvirus genus, one of most abundant groups of plant viruses, which displays a very wide host range. We have studied by cryoEM the structure of TuMV virions and its viral-like particles (VLPs) to explore the role of the interactions between proteins and RNA in the assembly of the virions. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 25 publications
6
41
0
Order By: Relevance
“…To examine if CP provided in trans could rescue the movement defect of TuMV CP deletion or point-mutation mutants, we generated transgenic Arabidopsis plants overexpressing TuMV CP and then inoculated them with the movement-defective TuMV CP mutants. We confirmed CP expression in these plants ( Figure 7), and observed VLPs in these transgenic plants, in agreement with recently published data (Cuesta et al, 2019). To our surprise, we found that overexpression of CP failed to rescue these movement-defective mutants (Figure 7).…”
Section: The Cis-expression Of Cp Is Essential For Tumv Translocatisupporting
confidence: 92%
See 4 more Smart Citations
“…To examine if CP provided in trans could rescue the movement defect of TuMV CP deletion or point-mutation mutants, we generated transgenic Arabidopsis plants overexpressing TuMV CP and then inoculated them with the movement-defective TuMV CP mutants. We confirmed CP expression in these plants ( Figure 7), and observed VLPs in these transgenic plants, in agreement with recently published data (Cuesta et al, 2019). To our surprise, we found that overexpression of CP failed to rescue these movement-defective mutants (Figure 7).…”
Section: The Cis-expression Of Cp Is Essential For Tumv Translocatisupporting
confidence: 92%
“…Considering that the fluorescent protein tag might negatively affect the CP interactome and virion assembly in plants, we chose the plant expression vector pEarleyGate100 (Early et al, 2006), which contains no fluorescent protein tag, to generate the CP expression vector for genetic transformation of Arabidopsis. After confirmation of the expression of the TuMV CP by immunoblotting and RT-PCR (Figure 7a), we observed virus-like particles (VLPs) with various lengths in those CP-expressing transgenic plants, consistent with a recent report (Cuesta et al, 2019).…”
Section: Cp Expressed In Cis Not In Trans Functions In Viral Cell-tsupporting
confidence: 91%
See 3 more Smart Citations